Penerapan Teknologi AI Guna Pembangunan Tempat Pembuangan Sampah Sesuai Jenisnya - Said Teguh Putra Ramadhan; Muhammad Ilham; Sudy Sudy; Surya Tjahyadi; Nafisatul Hasanah; Justin Chua (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2023)
Abstract Garbage is a part of human life. Garbage is an object / residual substance that is not used. Garbage should receive serious attention and handling. However, there are still many people who just throw away their waste at will, such as throwing wet waste into a dry trash can, which makes processing the waste difficult. Currently, most people are aware of the bad effects of waste, including causing flooding, disease and odors that can interfere with life. But this is not matched by the behavior of the people themselves. The purpose of this study is to try to find a way out of environmental sanitation problems, especially waste management. We also want people to be able to differentiate between organic waste and non-organic waste. Because there are still many people who do not know what kind of waste is classified into organic waste and non-organic waste. With the development of an increasingly sophisticated era, the use of Artificial Intelligence is expected to be able to crush the existing waste problem. Keywords: Garbage, Environmental Sanitation, Organic, Non-Organic